Methods, Models and Tools for Fault Tolerance - Butler, Michael; Jones, Cliff B.; Romanovsky, Alexander; Troubitsyna, Elena (Programming and Software Engineering, 2009)
The growing complexity of modern software systems makes it increasingly difficult to ensure the overall dependability of software-intensive systems. Mastering system complexity requires design techniques that support clear thinking and rigorous validation and verification. Formal design methods together with fault-tolerant design techniques help to achieve this. Therefore, there is a clear need for methods that enable rigorous modeling and the development of complex fault-tolerant systems. This book is an outcome of the workshop on Methods, Models and Tools for Fault Tolerance, MeMoT 2007, held in conjunction with the 6th international conference on Integrated Formal Methods, iFM 2007, in Oxford, UK, in July 2007. The authors of the best workshop papers were asked to enhance and expand their work, and a number of well-established researchers working in the area contributed invited chapters in addition. From the 15 refereed and revised papers presented, 12 are versions reworked from the workshop and 3 papers are invited. The articles are organized in four topical sections on: formal reasoning about fault-tolerant systems and protocols; fault tolerance: modelling in B; fault tolerance in system development process; and fault-tolerant applications.